Research Review: Do parent ratings of infant negative emotionality and self‐regulation predict psychopathology in childhood and adolescence? A systematic review and meta‐analysis of prospective longitudinal studies. (6th November 2019) - Kostyrka‐Allchorne, Katarzyna; Wass, Sam V.; Sonuga‐Barke, Edmund J. S.
Abstract : Background: Identifying low‐cost and easy to implement measures of infant markers of later psychopathology may improve targeting of early intervention for prevention. Because of their early manifestation, relative stability and overlap with constructs central to affect‐based dimensions of child and adolescent psychopathology, negative emotionality and self‐regulation have been the focus of this research. We conducted a meta‐analysis of longitudinal studies examining the prospective association between infant temperament measured with parent ratings and child/adolescent psychopathology. Methods: A systematic literature search for prospective longitudinal studies, which included measures of questionnaire‐assessed infant temperament (negative emotionality, self‐regulation, behavioural inhibition, surgency/extraversion, activity level) and symptoms of child or adolescent mental health (externalising, internalising) and neurodevelopmental problems (attention deficit/hyperactivity disorder [ADHD], autism spectrum disorder [ASD]), was conducted. Standardised estimates of association were calculated and pooled in meta‐analyses. Results: Twenty‐five studies ( n  = 28, 425) met inclusion criteria. Small associations were seen between psychopathology aggregated across all domains and infant negative emotionality ( r  = .15; p  < .001) and self‐regulation ( r  = −.19; p  = .007). Effects were also significant but weaker for behavioural inhibition ( r  = .10; p  = .027) and activity level ( r  = .08; p  = .016). Surgency/extraversion was not significantly associated with psychopathology in general ( r  = −.04; p  = .094); however, it was negatively associated with ASD ( r  = −.10, p  = .015). Significant correlations were observed with some outcomes isomorphic with predictors, internalising problems and behavioural inhibition ( r  = .10; p  = .013), ADHD symptoms and activity level ( r  = .19; p  = .009). Conclusion: Questionnaire‐based assessments of infant negative emotionality may have transdiagnostic potential to contribute to a risk index of later childhood psychopathology. Behavioural inhibition, surgency/extraversion and activity ratings may provide more specific predictive power. More data from prospective studies are required before the potential of self‐regulation and surgency/extraversion can be properly gauged.